Still a nation of immigrants - Ashabranner, Brent K., 1921- (New York : Dutton, 1993)
Identifies who today's immigrants to the United States are, describes their experiences, contributions, and impact on society, and discusses how an immigrant becomes a citizen.
Includes bibliographical references (p. 127-128) and index.
Booklist.
Wilson's Children.
Wilson's Junior High School.
7.3
5-8
Keywords: Immigrants -- United States -- Juvenile literature; Immigrants; Immigration and emigration; United States -- Emigration and immigration -- Juvenile literature; United States -- Emigration and immigration; United States -- Immigration and emigration